DETERMINING THE DIRECT RESISTANCE COEFFICIENT OF COTTON FIBER IN THE CONFUSOR TUBE - Korabayev, Sherzod (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
This study focuses on determining the direct resistance coefficient of cotton fibers within a conical confusor tube, which is essential for optimizing rotor spinning processes. By employing mathematical modeling and computational fluid dynamics (CFD), the study investigates how airflow characteristics impact fiber behavior. The resistance coefficient, Cx, was calculated from experimental data and compared with theoretical models for both laminar and turbulent flows. The effects of key parameters, such as Reynolds number and airflow velocity, on fiber resistance were analyzed. The findings indicate that an increase in airflow velocity results in a decrease in the direct resistance coefficient. The research highlights the influence of geometric factors in the confusor on fiber dynamics and yarn quality, providing insights for enhancing rotor spinning efficiency.